An analytical study of the competitiveness of the economies of the United Arab Emirates during the period: “2012-2022” - Nawal, Hani; Dalila, Berkane; Kerdoudi, Sabrina; Belaghlem, Noureddine; Chechem, Hafida (The International tax journal, 2025)
The study aims to shed the light on the issue of competitiveness, which has become increasingly important in light of globalization, where economic growth has become extremely difficult issue for some countries to integrate into the global economy, and achieving advanced levels in the ranking of global reports on the competitiveness of global economies. For this, the study attempts to determine the competitive position of the United Arab Emirates economy in the global competitiveness report according to the World Economic Forum during the period 2012-2022 by measuring some indicators. One of the most significant outcomes of the study is that the United Arab Emirates’ economic indicators ranked first in the Arab world and advanced internationally according to the World Economic Forum report during the study period.